Production of Peptone from Enzymatic Hydrolysates of Chicken Feather Keratin and Use as an Alternative Source of Nitrogen in the Preparation of Some Medium - Yasmin.k.AL-rubaie; Elham.I.AL-Shamary (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study aimed to use chicken feathers to reduce environmental pollution in the preparation of expensive peptone and use it as an alternative source of nitrogen in the preparation of some media for the growth of some microorganisms. The results showed that the chicken feather powder contained 4.12, 87.05, 5.12, 1.01 and 2.70% moisture, protein, ash, fat and carbohydrates. The results also showed that the keratin was decomposed by pepsin and chymotrypsin enzymes, and the best degree of decomposition obtained was 30% after 30 hours of decomposition using chymotrypsin enzyme. It was also found that the lowest solubility was obtained at pH (3, 4) and the best solubility was (30, 39, 50, 50.3 and 50.6) at pH numbers (5, 6, 7, 8 and 9). It was also noted that the highest water holding capacity was 3.50 at pH 7 for keratin hydrolysate using chymotrypsin enzyme after 30 hours of hydrolysis. The numbers of Bacillus subtilis and Staph aureus reached (141, 117) × 105 and (100, 89) × 105 and (135, 110) × 105 in the solid nutrient medium and the modified media with the addition of keratin hydrolysate after 24 and 30 hours of hydrolysis using chymotrypsin enzyme. However, the numbers of E.coli and Salmonella typhi reached (75, 54)× 105, (34, 14)× 105, (54, 35)× 105 respectively, in the commercial and modified MacConky agar medium.